Healthcare Norms under Universal Healthcare (UHC) for Maharashtra: Relieving Illness and Ensuring Public Health. (December 2016) - George, Mathew
Healthcare norms of a nation also reflect the extent of preventive, promotive, curative and rehabilitative services that is expected to be delivered by a nation's health services system. It is a reflection of the model of healthcare delivery proposed, whether it is a physician-intensive model where the doctor requirement for a population is much higher than a community-health-worker-based model. Healthcare norms need to be differentiated from human resource requirement for health as the latter largely revolves around the professional to population ratio, which not only fail to consider inequities in the regional distribution of health personnel but also undermine the institutional level strengthening required for effective delivery of services. Thus, the present article is an attempt to propose a healthcare norm for the state of Maharashtra. This article will have two parts, first is the curative component, which is proposed based on the projected morbidity prevalence of the population, and the second part is the norm for a public health system competent enough to address the essential public health functions.